“NEW ANDEAN FIGURATIVISM” - THE CURRENT LANDSCAPE IN AYACUCHA PAINTING 2000 – 2020 - Meza Untiveros, Miguel Angel (2024)
In the Ayacucho region, in the mid-20th century, the "Felipe Guamán Poma de Ayala" School of Fine Arts was founded, with the aim of training pictorial artists who value and represent their culture, influenced and referenced by different trends and pictorial styles; On the other hand, currently the founding teachers and graduates are part of the Ayacucho pictorial expression. In this sense, landscape painting developed its own characteristics, taking on historical, social and cultural aspects of a local, national and international nature; In this way, it is proposed to generate a significant value to Ayacuchano landscape painting between the years 2000 and 2020, taking into account its background and development to call it "New Andean Figurative Art". Thus evidencing the various techniques used, the symbolism in the form, content and message around the socio-cultural context of the region. In this way, the following question is posed: What does landscape painting express in Ayacucho? To respond, a visual analysis methodology will be used, developing an iconographic and iconological study of each of the works to be investigated. On the other hand, it is hypothesized, to what extent does landscape painting in Ayacucho express traditional values ​​and local customs?